PENGARUH KONSELING TERHADAP PENINGKATAN PENGETAHUAN PENDERITA HIPERTENSI DALAM PENGENDALIAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS ANAK AIR PADANG 2017 - -, Nurhamidah Rahman (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Based on WHO data in the year (2014), there are about 600 million people with hypertensionworldwide. In the City Health Service report 2016, obtained from 22 health centers in the cityof Padang. Anak Air Public Health is the highest health center visited by hypertensionpatients. The number of hypertensive patients in the Working Area of Anak Air Public Healthis 475 people. The purpose of this study is to determine the effect of health promotion bycounseling method to increase knowledge of hypertensive patients in controlling hypertensiondisease in Batipuh Panjang Village Working Area Puskesmas Anak Air Padang Year 2017.This type of research is quasi experiment with one group pretest-posttest design design inBatipuh Panjang Village Working Area of Anak Air Public Health using simple randomsampling technique. The sample size is 36 respondents. Data collection using questionnaireswith guided interviews. Then the data is processed using wilcoxon test. Based on statistical testthere is influence of counseling to increase knowledge of hypertension patient in hypertensiondisease control with value of p <0,05.Based on the results obtained, it is expected to health workers to improve health promotion inthe form of counseling and services in providing information to the community abouthypertension.Keywords: counseling, knowledge, hypertension